Perception of faraid among UiTM Cawangan Selangor, Kampus Puncak Alam students / Muhammad Nasir Jamaluddin. - Jamaluddin, Muhammad Nasir (2019)
Faraid is one of the first knowledge that God will take back from humans. This has shown that faraid knowledge is very important. It is because of the attitude do not concerned of Muslims today that this knowledge of faraid has been lost in the ages leading to misunderstandings and disputes regarding faraid, and there are some who doubt in God's justice such as the men is get two times more portion than women's in faraid. The purpose of this study was to identify the level of perception of respondents towards faraid, to identify perceptual differences in terms of gender, course and semester. Respondents for this study were to ACIS students, UiTM session 2019/2020. The research instrument used was a questionnaire developed from google form and consisted of 12 question items. The reliability of the study tool is α = 0.748 which is high.The findings of the study as a whole indicate that respondents' perception of management and justice is at the medium high level. At the end of the study, there are several suggestions were made to improve the faraid management system to responsible bodies and th the responsibilities of lecturers in educating students about faraid. Further studies are also proposed for future research.